An Examination of the organizational drivers for internal audit value addition of large firms within Nairobi County, Kenya - Gatungo, Judith Njeri (Strathmore University, 2019)
Internal audit has revolved to be a vital function within organizations; many organizations are therefore showing more concern to their internal auditors to give proper guidance and advice at the various levels of management. This is because of the important role that the internal audit plays in the processes ongoing in the organization, the IA is expected to have a value adding component while serving as a vital strategic partner in addition to providing the usual assurance services. This study therefore, sought to explore how various variables create value to the internal audit activities. The study was guided by the following objectives that were applied in the study: - Objectives being; to establish role that management and board support as an influence to the internal audit in adding value to the organization, to establish the contribution of communication on internal audit value addition and to study the importance of competence on internal audit value addition within listed firms in the NSE with an aim of recommending win-win strategies for the stakeholders. The study adopted the descriptive research design characterized by a systematic collection of data from respondents through questionnaires. The collected data was analyzed using factor analysis technique, correlation and regression. 108 questionnaires were distributed to 34 listed companies that represented 80% of the targeted population. The three categories of factors had an influence on internal audit value addition with management support, adequacy of auditor competence and effective communication were found to have a positive significant relationship in the influence of internal audit value addition. This study highlighted the need for listed Kenyan companies to identify organizational drivers that influence internal value addition and put emphasis to them. Findings from this study will help management, internal auditors as well as external auditors on ensuring that they add value to their work.
A thesis submitted in partial fulfillment of the requirement for the Degree of Master of Commerce at Strathmore University
Keywords: Organizational drivers; Internal audit value addition; Nairobi County, Kenya